Clinical and pre-clinical investigation of sertraline use in pregnancy: bioavailability and risk to offspring - Phogole, Cassius Maapea (Stellenbosch : Stellenbosch University, 2025)
Phogole, C. M. 2025. Clinical and pre-clinical investigation of sertraline use in pregnancy: bioavailability and risk to offspring. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/09f65288-4b2f-4c4a-96d2-c21eba79bef4